2002
DOI: 10.1007/s004140100220
|View full text |Cite
|
Sign up to set email alerts
|

Determination of firing distance using the rhodizonate staining technique

Abstract: The histological staining technique using rhodizonate is also effective for the determination of the firing distance by examining the distribution and intensity of the staining reaction. The differentiation between absolute close-range shots and long-range shots is generally possible without any doubt. The method is not recommended for routine examinations but it is very useful for cases lacking the possibility to investigate smoke and powder deposits in a criminalistic manner, i.e. surgical skin biopsies of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 10 publications
2
21
0
2
Order By: Relevance
“…Moreover, this method has the potential to provide quantifiable, measurable, and comparable evidence for estimation of the shooting distances in the reconstruction of events in gunshot fatalities [16,24,25]. Our contribution confirmed the previous results obtained in experimental scenarios [14] showing that the amount and the spatial distribution of GSR deposits in the skin surrounding entrance wounds strictly correlate with shooting distance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, this method has the potential to provide quantifiable, measurable, and comparable evidence for estimation of the shooting distances in the reconstruction of events in gunshot fatalities [16,24,25]. Our contribution confirmed the previous results obtained in experimental scenarios [14] showing that the amount and the spatial distribution of GSR deposits in the skin surrounding entrance wounds strictly correlate with shooting distance.…”
Section: Discussionsupporting
confidence: 91%
“…Smoke stain and interspersions of gunpowder are important histological findings that can be visualized quite well in histological sections by their own coloration without special treatment [18]. After the experimental study carried out by Marty et al [14] who demonstrated that differentiating between the different range shots is possible with the assessment of the distribution of sodium rhodizonatepositive primer particles on and in tissue, we compared the different pattern of sodium rhodizonate-positive deposits with the shooting distance, reliably known by macroscopic and histological characteristics of entrance wounds. The histological sections were also analyzed with a confocal laser scanning microscope.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The undermining of the periosteum may exceed the area of intense soot soiling by a few centimeters. However, in these peripheral parts the periosteal surface does not show homogenous soot blackening, but dispersed gunshot residues, similar to the scattered deposits which are seen on the surface of the entrance site in close-range shots [12].…”
Section: Discussionmentioning
confidence: 96%